Social structure - social learning and delinquency: mediation or moderation? - Verrill, Stephen W. (Criminal justice recent scholarship, 2008)
Social learning theory -- Social structure-social learning -- Crime rate determinants XE "crime rate determinants" -- Research design and analytic strategy -- The case for moderating effects -- Reconciliation of previous literature -- Future research